Understanding the “Empty Box” Phenomenon in Indonesian Electoral Politics: A Study of Simultaneous Regional Elections - Mahpudin; Wawan (JIAPI: Jurnal Ilmu Administrasi Dan Pemerintahan Indonesia, 2025)
This article examines the dilemma surrounding the use of “empty columns” in Indonesia’s local elections (Pilkada). Empty columns were introduced during the 2017 simultaneous regional elections in response to the rising number of uncontested races, where only a single candidate pair appeared on the ballot. Such races have increased in each electoral cycle, with 25 single-candidate contests occurring in 2020. Although empty columns were designed to preserve democratic contestation by ensuring voters have at least two options, the regulatory and political framework governing them remains fragile. This study aims to explain why empty columns have become a dilemma within contemporary electoral political discourse. This research employs a qualitative methodology with an exploratory analytical approach, drawing on empirical patterns identified through an extensive review of relevant literature. The findings indicate that the empty column represents a fundamentally contradictory mechanism: while it is formally intended to sustain competition, it lacks the political infrastructure necessary for effective contestation and thus functions as a nominal rather than substantive electoral alternative. As a result, empty columns are structurally disadvantaged and struggle to counterbalance the dominance of single-candidate pairs, ultimately undermining their intended role in strengthening democratic practice.